2017
DOI: 10.1002/anie.201706060
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Tail‐Tube Assembly Studied by Proton‐Detected 4D Solid‐State NMR

Abstract: Obtaining unambiguous resonance assignments remains a major bottleneck in solid‐state NMR studies of protein structure and dynamics. Particularly for supramolecular assemblies with large subunits (>150 residues), the analysis of crowded spectral data presents a challenge, even if three‐dimensional (3D) spectra are used. Here, we present a proton‐detected 4D solid‐state NMR assignment procedure that is tailored for large assemblies. The key to recording 4D spectra with three indirect carbon or nitrogen dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…To check the significance of this newly discovered interface, we removed the last 7 and 14 C‐terminal residues of gp17.1 (1–170 and 1–163) and observed that both mutants are incapable of polymerization, but remain monomeric (see size‐exclusion chromatography data in Figure S5 and solution NMR data in Figure S6 in the Supporting Information) . This emphasizes the proposition that the C‐terminus forms a molecular bridge that embraces the next monomer within the tube, similar to what was described for the N‐terminus of the T4 phage tail tube protein gp19 …”
Section: Figuresupporting
confidence: 55%
“…To check the significance of this newly discovered interface, we removed the last 7 and 14 C‐terminal residues of gp17.1 (1–170 and 1–163) and observed that both mutants are incapable of polymerization, but remain monomeric (see size‐exclusion chromatography data in Figure S5 and solution NMR data in Figure S6 in the Supporting Information) . This emphasizes the proposition that the C‐terminus forms a molecular bridge that embraces the next monomer within the tube, similar to what was described for the N‐terminus of the T4 phage tail tube protein gp19 …”
Section: Figuresupporting
confidence: 55%
“…The ratio between the first contour level and the noise in the projections are set to be the same in every projection, but is different in the uniformly sampled experiments shown in Figure . The goal of performing a lower‐dimensionality uniformly sampled experiment is to confirm that no artifacts are accidentally used in the analysis (or presented above the height of the first contour as defined). We chose to compare the nine schedules by using a similar number of FID scans, emphasizing the difference in time saving when reducing the coverage schedule.…”
Section: Resultsmentioning
confidence: 99%
“…After dialysis gp17.1 was left for 3 weeks at room temperature to polymerize. The gp17.1 filaments were sedimented by ultracentrifugation at 90,000 × g for 2 h. 100 mg of gp17.1 protein pellet could be isolated 16 . For methyl-labeling, 12 C 6 ,D 7 -glucose was used instead of 13 C 6 ,D 7 -glucose and specific precursor molecules were supplied to the bacterial cultures 1 h prior to induction (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…However, virions only containing gp17.1 are still viable and infectious, indicating that the additional C-terminal FN3 domain is dispensable for phage assembly and infection 15 . gp17.1 monomers are unstable in solution and spontaneously self-polymerize into long tubes in vitro which are indistinguishable from native tubes 6,16 . Previously, we presented the proton-detected solid-state NMR (ssNMR) assignment of deuterated, 100% back-exchanged gp17.1 tubes and deduced secondary structure information from the assigned chemical shifts, which confirmed and extended an existing homology model of a polymerized gp17.1 subunit 6,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation